The need to increase the innovative and investment activity of small businesses and entrepreneurs in the Republic of Uzbekistan (Eurasian Journal of Media and Communications, 2021)
The article discusses the theoretical issues of increasing the innovation and investment activity of small businesses in the transition to a digital economy and the content of key terms encountered in this process, the conditions created in our country, the main problems and proposals